Political Transformation of Islamic Law in the Context of National Family Law: Between Idealism and Reality - Hopipah, Eva Nur; Safe'i, Abdulah; Astarudin, Tatang (Institut Agama Islam Negeri Kerinci, 2023)
The era continues to move dynamically, whether towards positive change or the opposite, making transformation inevitable. In this process, numerous political processes occur, especially in the transformation of Islamic law within the current national family law as manifested in Marriage Law Number 1 of 1974 and other legislations. It needs to be comprehensively understood regarding the transformation process from classical/conventional Islamic law to the emergence of ijtihad (ijma'), giving birth to the Compilation of Islamic Law (KHI). There is a contradiction between idealism and the reality that occurs in the transformation of Islamic law. This research addresses essential questions about how the political process occurs in the transformation to legislation. The method used in this study is literature review with primary sources being books or articles related to Islamic law, political aspects of Islamic family law, transformation and reform of Islamic law, contemporary family law, and other relevant sources as secondary sources. The results of this research prove that there are crucial points in the transformation of Islamic law into national family law related to marriage, divorce, inheritance, and endowment, which still require further integration to review the realities that occur in the field.